2014
DOI: 10.1152/ajpheart.00901.2013
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle microvascular oxygenation dynamics in heart failure: exercise training and nitric oxide-mediated function

Abstract: Chronic heart failure (CHF) impairs nitric oxide (NO)-mediated regulation of skeletal muscle O2 delivery-utilization matching such that microvascular oxygenation falls faster (i.e., speeds PO2mv kinetics) during increases in metabolic demand. Conversely, exercise training improves (slows) muscle PO2mv kinetics following contractions onset in healthy young individuals via NO-dependent mechanisms. We tested the hypothesis that exercise training would improve contracting muscle microvascular oxygenation in CHF ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 71 publications
(118 reference statements)
2
42
0
Order By: Relevance
“…Hirai and colleagues (59) reported that, in healthy rats, progressive moderate to vigorous downhill running endurance EX improved microvascular oxygenation profiles following the onset of skeletal muscle contraction, partially through an NO mechanism. Furthermore, similar improvements were observed in rats with chronic heart failure but did not appear to be NO mediated (60). Interestingly, in the aforementioned studies, EX augmented soleus and red gastrocnemius citrate synthase content, but only in the latter study did citrate synthase content increase in the spinotrapezius muscle, the skeletal muscle where microvascular oxygenation was examined.…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodsupporting
confidence: 52%
“…Hirai and colleagues (59) reported that, in healthy rats, progressive moderate to vigorous downhill running endurance EX improved microvascular oxygenation profiles following the onset of skeletal muscle contraction, partially through an NO mechanism. Furthermore, similar improvements were observed in rats with chronic heart failure but did not appear to be NO mediated (60). Interestingly, in the aforementioned studies, EX augmented soleus and red gastrocnemius citrate synthase content, but only in the latter study did citrate synthase content increase in the spinotrapezius muscle, the skeletal muscle where microvascular oxygenation was examined.…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodsupporting
confidence: 52%
“…Remarkably, that no substantial impairments in Hct cap were detected across the rest-contraction transient in HFrEF indicates that effective capillary surface area at any given time was lowered in approximate proportion to the reduction in capillaries sustaining RBC flow. Taken together, these investigations demonstrate that HFrEF is associated with pronounced impairments in skeletal muscle transcapillary O 2 flux via reductions in both diffusive (i.e., D mO 2 ; 2number of RBC flowing capillaries per unit muscle width x ↔Hct cap ) and convective (i.e., Q mO 2 ; 2number of RBC flowing capillaries per unit muscle width x 2f RBC ) conductances (162,257 (30,58,59,65,78,136,206) are thus associated with impairments in mitochondrial energetics and contractile performance (138,164,294,323).…”
Section: H1426 Exercise Training and Muscle O2 Transport And Utilizatmentioning
confidence: 80%
“…In addition, blockade of nitric oxide synthase (NOS) by nitro-L-arginine methyl ester (L-NAME) reveals that the NOS contribution to Q mO 2 -to-V mO 2 matching in healthy muscle is substantially reduced in HFrEF. As the NOS enzymes are upregulated by exercise training (134,136; for a review, see Ref. 188), this, in addition to reduced oxidative stress, decreased sympathetic and humorally mediated vasoconstriction, and improved vascularity (capillary and arteriolar; see Fig.…”
Section: Exercising Blood-muscle O 2 Flux In Health and Chf: Mechanismentioning
confidence: 99%
See 2 more Smart Citations